Solution processable single-walled carbon nanotubes based thin film field-effect transistors - Chen, Simin. (2010)
Single-walled nanotubes (SWNTs) has a unique varying band gap make them one of the choices for fabricating high-performance thin film field-effect transistors by dispersing SWNTs in array to form the conducting channel. The substrate surface plays an important role in solution processable thin film transistors to selectively interact with semiconducting SWNTs in order to obtain better electrical properties. In this work, the surfaces of silicon thermal oxide were functionalized with silanes before SWNTs suspension drop casting. It was found that dip coating in 1% silane-methanol solution followed by baking can provide clean surface with better properties. The functional groups in silanes were suspected to affect the interaction with SWNTs greatly indicated by different electrical properties obtained. Other factors including SWNTs solution and transistor channel configurations also collaborated in providing certain transistor properties. In addition, a thin layer of polymethyl-methacrylate (PMMA) was found to improve performance regardless of silanes functionalized groups, the on/off ratio achieved was up to 6 orders of magnitude and the mobility could be as high as 15.6 cm2/Vs.